(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
Our study deals with preparation of two types of imine compounds differ in the type of terminal group, where one of them has a terminal carboxyl group COOH while the other contains methoxyOCH3 as a terminal group. In the first part of this research it was Identification by spectroscopy methods using infrared IR and nuclear magnetic resonance H NMR spectrum, besides elemental analysis shows the exact chemical structure of the expected synthesized compounds. In the second part was the study of liquid-crystalline behavior by polarized optical microscopy POM and differential scanning calorimetry DSC that showed a liquid crystal phase in the compounds that has odd number of carbon atoms in the terminal chain compounds in the first series, while the second series compounds showed liquid crystal phase in the compounds that containing even number of atoms of carbon in the terminal chain.